Investigating Students’ Obstacles in English Learning on Speaking Skill at Mts Miftahul Ulum Gondanglegi: English - Maura Sela Azizah; Mulis (JELP Journal of English Language and Pedagogy, 2023)
The paper aims at investigating the students’ obstacles in English learning on speaking skill. The research design in this study was a descriptive with qualitative paradigm. The subjects of this study were eight grade class consisting of 28 students at MTs. Miftahul Ulum Gondanglegi. The research instruments applied in this research were questionnaires and interviews. The questionnaires were distributed to the students, while the interview was conducted with the English teacher. The results of this research revealed that the students faced two main obstacles in speaking skill; students’ language skill and students’ phycological obstacles. In terms of students’ language skill, the students faced poor in vocabulary obstacle, poor in grammar obstacle, poor in pronunciation obstacle. While related to students’ phycological challenges, they encountered challenges such as fear of making mistakes, having shyness, feeling anxiety, lack of confidence, and lack of motivation.